Predictor of Left Atrial Spontaneous Echocardiographic Contrast in Rheumatic Mitral Stenosis Patients - Komaria, Komaria; Halim R, Abdul; Nst, Ali Nafiah; Hasan, Harris (Indonesian Journal of Cardiology, 2017)
Background: Previously conducted researches showed that presence of SEC in the left atrium can constitute a risk factor for thrombus formation. Some previous studies have also reported that in addition to atrial fibrillation and blood stasis in the left atrium, the pathophysiology of left atrial thrombus and SEC occurring in patients with rheumatic mitral stenosis exhibits some other mechanisms, such as autoimmunity, inflammation and increased thrombotic activity. Methods: Cross sectional study was conducted between July 2015 to July 2017 in patient who admitted to Haji Adam Malik Hospital due to rheumatic mitral stenosis. They were divided into two groups according to presence of left atrial SEC. Result: From 104 patients, 52 (mean age 40 ± 11 years; 71,2% women) were in the left atrial SEC-negative group and 52 patients (mean age 40 ± 10 years; 73,1% women) were in the left atrial SEC-positive group. There were no significant differences in the leucocyte, 8,06±1,54 were in the left atrial SEC-negative group and 7,37±1,76 were in the left atrial SEC-positive group. In multivariate analysis, atrial fibrillation (OR = 51,311, 95% CI 3,723 – 707,100, p = 0,003) neutrophil/lymphocyte ratio (OR = 21,641, 95% CI 5,174 – 90,528, p < 0,001), mitral valve area (OR = 14,423, 95% CI 1,665 – 124,908, p = 0,015), and RDW (OR = 5,743, 95% CI 1,349 – 24,445, p = 0,018), These study show that neutrophil/lymphocyte ratio with cut off point of >3,2 had sensitivity, spesificity, positive predictive value, and negative predictive value to predict left atrial SEC is the same 81%, respectively. Conclusion: Atrial fibrillation, neutrophil/lymphocyte ratio, RDW and mitral valve area can predict left atrial spontaneous echocardiographic contrast in rheumatic mitral stenosis patients.   Abstrak Latar Belakang: Penelitian sebelumnya menunjukkan adanya SEC di atrium kiri menjadi faktor risiko untuk pembentukan trombus. Pada pasien stenosis mitral rematik, risiko trombosis dan perkembangan SEC di atrium kiri tinggi. Beberapa penelitian sebelumnya melaporkan bahwa patofisiologi trombus dan SEC di atrium kiri selain fibrilasi atrium dan stasis aliran darah di atrium kiri juga adanya beberapa mekanisme lain seperti respon imun, inflamasi dan peningkatan aktifitas trombotik. Metode: Ini adalah penelitian observasional yang bersifat cross sectional, dilakukan dari Juli 2015 sampai Juli 2017 terhadap pasien stenosis mitral rematik yang datang ke rumah sakit Haji Adam Malik. Pasien dibagi 2 kelompok berdasarkan kehadiran SEC di atrium kiri menurut hasil pemeriksaan ekokardiografi. Hasil: Didapatkan 104 pasien, dimana 52 pasien (usia rata-rata 40 ± 11 tahun, 71% wanita) merupakan kelompok tanpa SEC, dan 52 pasien (usia rata-rata 40 ± 10 tahun, 73% wanita) merupakan kelompok dengan SEC. Tidak ada perbedaan bermakna pada lekosit, dimana kelompok tanpa SEC (8,06±1,54) dan kelompok dengan SEC (7,37±1,76). Dari analisis multivariat regresi logistik, didapatkan fibrilasi atrium (OR = 51,311, nilai IK 95% antara 3,723 – 707,100, p = 0,003) rasio netrofil/limfosit (OR = 21,641, nilai IK 95% antara 5,174 – 90,528, nilai p < 0,001), area katup mitral (OR = 14,423, nilai IK 95% antara 1,665 – 124,908, nilai p = 0,015), dan RDW (OR = 5,743, nilai IK 95% antara 1,349 – 24,445, nilai p = 0,018), merupakan prediktor independen untuk terjadinya SEC. Titik potong untuk nilai rasio N/L > 3,2 memiliki angka sensitivitas, sensitifitas, nilai prediktif positif dan nilai prediktif negatif yang sama yaitu masing-masing 81% untuk memprediksi kejadian SEC di atrium kiri pada pasien stenosis mitral rematik. Kesimpulan: Fibrilasi atrium, rasio netrofil/limfosit, RDW dan area katup mitral dapat menjadi prediktor SEC di atrium kiri pada pasien stenosis mitral rematik.